Sociometric structure of premier league volleyball club - Vojvodic, M.; Jovanovic, M. (SportLogia, 2014)
For the investigation of interpersonal relations in small groups such as sports, sociometric procedure are used. In this study, sociometric procedure is conducted and sociometric structure has been made for the female University Volleyball Club BL volley from Banja Luka, who competes in the Premier League BiH. The task was to discover the emotional-social and functional status of the players, and the status of congruency and to evaluate the atmosphere at the club. Further analysis has been done of the aspirations of the players in terms of taking a position at the score table, as well as their assessment of management's expectations regarding the position on the score table. After sociogram and sociometric matrices has been made, it can be said that the team has three distinctive groups that are separated by mutual election of its members when it comes to emotional and sociological status. The assessment of functional status identifies two players who received 16 and 14 votes out of 17 possible. Two players who have received the most votes by socio-emotional criteria, were not selected in the first team by the coplayers, which again speaks of a team that very well makes a distinction between "friendship and business". Based on these results, it can be concluded that the atmosphere in the team is good and that it is not affected by functional status, or age of the players (almost half of the team is younger than 18). And finally, using Man-Vitni and Kruskal-Volis test it was found that neither age nor functional status does not affect significantly the assessment of the position on the score table. Functional status and age is also not a source of significant differences in the assessment of the players on what they think the club management is expected from them.